CENTRAL HEMODYNAMICS AND PARASYMPATHETIC TONE IN PARTURIENTS UNDERGOING CESAREAN SECTION UNDER SPINAL ANESTHESIA - Батюк, Андрей Мирославович; Плотников, Георгий Павлович; Пугачев, Станислав Валерьевич; Коченкова, Наталья Евгеньевна; Веселкова, Ольга Вадимовна; Новикова, Оксана Николаевна; Григорьев, Евгений Валерьевич (Medicine in Kuzbass, 2017)
Objective – to optimize therapy and prevention of arterial hypotension caused by spinal anesthesia during Cesarean section. Methods. Pregnant women undergoing Caesarean section under spinal anesthesia were divided into two groups depending on the predominance of sympathetic or parasympathetic tone. A comparison of central haemodynamic parameters on the basis of non-invasive monitoring were perfomed. Results. Low cardiac output, arterial hypotension, bradycardia, consumption of vasopressors and cholinolitics were significantly more often observed in the group of patients with a predominance of parasympathetic tone. Conclusion. Considering the preoperative measurement of autonomic nervous system tone, pathogenetic approach to the treatment and prevention of arterial hypotension during Caesarean section with administration of atropine could be assumed instead of recommended routine application of adrenoagonists.